2016
DOI: 10.5152/ejp.2015.42714
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Restless Legs Syndrome on the Sleep Quality in Chronic Obstructive Pulmonary Disease

Abstract: Objective: It is well known that various sleep disorders are common in cases of chronic obstructive pulmonary disease (COPD). However, restless legs syndrome (RLS) has not been extensively studied in these patients. The aim of the current study was to investigate the prevalence of RLS and its impact on sleep quality in patients with COPD. Methods:The study included a total of 50 patients with COPD with a mean age of 67.2±7.7 years; 39 (78%) were male. The RLS diagnosis was made based on the questionnaire items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Similar results were obtained by Chen et al [33]. Additionally, In et al [34] and Abd El-Fattah et al [35] found negative correlation between PSQI and FEV1% and FVC. However, Scharf et al [36] found unremarkable difference regarding the relationship between FEV1% and sleep quality (PSQI) this controversy may be due to a limited group of their studied patients performed polysomnographic sleep study, so the objective determination of the prevalence of sleep breathing disorders is not presented.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were obtained by Chen et al [33]. Additionally, In et al [34] and Abd El-Fattah et al [35] found negative correlation between PSQI and FEV1% and FVC. However, Scharf et al [36] found unremarkable difference regarding the relationship between FEV1% and sleep quality (PSQI) this controversy may be due to a limited group of their studied patients performed polysomnographic sleep study, so the objective determination of the prevalence of sleep breathing disorders is not presented.…”
Section: Discussionsupporting
confidence: 84%
“…RLS was associated with poorer lung function in our study, similar to previously reported studies. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…), and other factors (OSA, BMI, restless legs syndrome, ward environment, etc.). At present, the research results of some influencing factors are not uniform, and the path between influencing factors and sleep quality also needs to be further explored through mediation research ( 38 , 57 61 ).…”
Section: Discussionmentioning
confidence: 99%